Does oral povidone-iodine therapy for critically ill patients in the intensive care unit provide any benefit in terms of preventing ventilator-associated pneumonia? - Mohammad Javad Ghazanfari; Mohammadreza Mobayen; Amir Emami Zeydi (Journal of Nursing Reports in Clinical Practice)
N/A